VBN 11 - A new high yielding and MYMV disease resistant blackgram variety - S. Geetha, R. P. Gnanamalar, N. Manivannan, A. Mahalingam, S. Lakshminarayanan, K. Bharathikumar, P. Ramakrishnan, M. Sudha, S. Marimuthu, V. K. Sathya, P. Ahila Devi, C. Vijayaraghavan, V. R. Saminathan and V. Ambethgar (Electronic Journal of Plant Breeding, 2020)
Blackgram variety VBN 11 (VBG 12-062) was derived from PU 31 x CO 6. It matures in 70 – 75 days. VBN 11 has a yield potential of 899 kg/ha. It is 14.8 and 11.8 % increased yield over VBN 6 (783 kg/ha) and VBN 8 (804 kg/ha) respectively. This variety has determinate plant type, medium duration with synchronized maturity and resistance to Mungbean Yellow Mosaic Virus (MYMV) disease and moderate resistance to powdery mildew disease. It is recommended for Kharif, Rabi and Summer seasons of Tamil Nadu. It was released by State Variety Release Committee during 2020 with the variety designation blackgram VBN 11.